The city from complex system theories. An approach to the study of Malaga urban area - Gallegos, Carlota Ángela Escudero (European Journal of Geography, 2017)
For almost 100 years ago, many authors have understood that cities are the most complex artifacts built by humans. The very idea of the city is coeval at the beginning of sedentary life and agriculture, in the early Neolithic period about 10,000 years ago. Although it is as old this type of human organization, continues to present a paradoxical problem as possibly all humans have the ability to recognize a city, just as we recognize a forest, even if we are unable to explicitly express our appreciation. In this article, we will try to make an approach to the state of the town of Malaga from the perspective of the theory of complex systems.